Optical Properties and Photochemical Transformation of the Dissolved Organic Matter Released by Sargassum - Powers, Leanne C.; Del Vecchio, Rossana; Blough, Neil V.; McDonald, Natasha; Schmitt-Kopplin, Philippe; Gonsior, Michael (Frontiers in Marine Science, 2020)
Chromophoric dissolved organic matter (CDOM) is the dominant absorber of ultraviolet radiation in the ocean, but its sources within the ocean, as well as its chemical composition, remain uncertain. One source of marine CDOM is Sargassum, an epipelagic marine macro brown alga common to the Gulf of Mexico, Caribbean, and Western North Atlantic. Furthermore, Sargassum contains phlorotannins, a class of polyphenols that may have similar optical properties to terrestrial polyphenols. Here, we analyze Sargassum CDOM optical properties, acquired from absorption and fluorescence spectra of filtered samples collected during Sargassum exudation experiments in seawater tanks. To further evaluate the structural basis of Sargassum CDOM optical properties, Sargassum CDOM was collected by solid phase extraction (SPE) and its chemical composition was tested by pH titration and sodium borohydride reduction. These chemical tests revealed that Sargassum CDOM absorption spectra respond similarly to pH titration and borohydride reduction when compared to terrestrially-derived materials, but Sargassum CDOM has unique absorbance peaks in difference spectra that have not been observed in terrestrially-derived CDOM. These absorbance features are consistent with the deprotonation of modified Sargassum phlorotannins, which are likely highly related phenolic acids and polyphenols. Sargassum CDOM was also more rapidly photodegraded when compared to terrestrial CDOM such as Suwannee River Natural Organic Matter. Similar to terrestrial DOM, ultrahigh resolution mass spectrometry revealed that sunlight decreases relative abundances of m/z ions and molecular formulas with an average O/C ratio of 0.6 and an average H/C ratio of 0.9, suggesting preferential photodegradation and/or phototransformation of hydrogen-deficient and oxygenated compounds, such as Sargassum phlorotannins. Assuming a large fraction of Sargassum CDOM is quickly mineralized to CO2 during its rapid photodegradation, Sargassum could play a major role in marine photochemical carbon mineralization during its annual growth cycle.